The Effectiveness of Family Support on Pregnancy related to Anxiety at Kepanjenkidul Primary Care in Blitar - Regina Firda Unzila; Ika Agustina (STIKes Patria Husada Blitar, 2020)
Pregnancy Related AnxietyÂ (PRA) is an anxiety felt by pregnant woman related to pregnancy. PRA is different from the general anxiety felt during pregnancy, and contributing to a greater risk of preterm birth. According to the survey at Kepanjenkidul Primary Care in Blitar City, there were 7 cases of preterm birth during 2017-2018. Family support could reduce the risk of PRA. Family support could make pregnant women calmer and relaxed during pregnancy. The purpose of this study was to determine the effectiveness of family support on the level of PRA at Kepanjenkidul Primary Care in Blitar. The study design was cross sectional, involved 50 respondents, chosen by accidental sampling. The data collected by PRAQ-R2 questionnaire used to measure PRA levels while social support questionnaire used to measure the support of family. The data was analyzed with Kendallâ€™s Tau. The results of the study showed that there was an effect of family support with anxiety levels by p value of 0.0001 <Î± 0.05. The study concluded there was an effect of family support on the level of pregnancy related to anxiety. The family supports could decrease the risk of pregnancy related to anxiety.